Determinant of Promotion Mix on Customer Retention of Melcom Products in Accra: Mediating role of Customer Satisfaction and Trust - Kur Akuei Kiir, Mayol (British Journal of Marketing Studies, 2024)
The study investigates the determinants of promotion mix on customer retention of Melcom products in Accra with a mediation of customer satisfaction and trust. The purposive sampling technique was used in selecting 260 customers of three Melcom Ghana branches i.e. Weija, Lapaz and Kaneshie in Accra.  The Statistical Package for Social Sciences (SPSS) version 20 was used in analyzing the data. The study revealed a significant association of sales promotion, advertising, public relation, direct marketing and customer satisfaction and trust. However, direct marketing was moderately found to be associated with customer satisfaction and trust. Also, customer satisfaction and trust was found to be significantly moderating promotional mix elements such as sales promotion, advertising, public relation, direct marketing and customer retention. Managerial implication was presented.